Cancer-associated fibroblasts: A multifaceted driver of breast cancer progression. Issue 2 (1st June 2015) - Luo, Haojun; Tu, Gang; Liu, Zhimin; Liu, Manran
Highlights We summarized clinical data referring to association among mammary CAFs markers, tumor characteristics and patients survival. We systemically reviewed the role of CAFs in breast cancer behaviors such as metastasis and therapeutic resistance. We reviewed the multifaceted and centric role of CAFs in mammary tumor microenvironment events.